Authority, Culture, and Sexuality in the Polygamy of Madurese Ulamas - Afandi, Moh.; Ramdlany, Ahmad Agus; Fauza, Nilna; Ula, Siti Khoirotul; Ubaidillah, Mohammad Farah (AHKAM : Jurnal Ilmu Syariah, 2024)
Generally, polygamy among Madurese Ulama is carried out arbitrarily and secretly, resulting in suffering and significant discrimination against women. However, in specific instances, certain Madurese Ulama exhibit unique behaviors in constructing polygamous families, fostering comfort and harmony within their households. This research investigates the practice of polygamy among the ulama of Madurese and the influencing factors behind such practices. Employing a qualitative method, primary data sources comprise three polygamous families led by Madurese Ulama, each demonstrating distinctiveness in managing their polygamous households. The findings of this study conclude the existence of two models of polygamy practiced by Madurese Ulama, including polygamy initiated by the husband's desire with consent from the wives and initiated by the wives with consent from the husband. The practice of polygamy among Madurese Ulama is influenced by factors such as sexual needs, the authority held by these Ulama, and the devout religious culture of Madurese society, which tends to venerate Madurese Ulama excessively. Abstrak: Pada umumnya poligami ulama Madura dilakukan secara sewenang-wenang dan siri (tidak dicatat oleh negara), yang mendatangkan penderitaaan dan diskriminasi yang sangat merugikan perempuan. Sebaliknya dalam fenomena tertentu, terdapat ulama Madura yang memiliki perilaku unik dalam membangun keluarga poligami sehingga mendatangkan kenyamanan dan keharmonisan dalam rumah tangga. Penelitian ini menelaah praktik poligami yang dilakukan oleh ulama Madura dan faktor yang mempengaruhi poligami tersebut. Penelitian ini menggunakan metode kualitatif dengan sumber data primernya adalah tiga keluarga ulama Madura yang memiliki keunikan dalam membagun rumah tangga poligamis. Hasil penelitian ini menyimpulkan bahwa terdapat dua model poligami yang dilakukan oleh ulama Madura, yaitu poligami yang dilakukan atas kehendak suami dengan persetujuan para istri dan poligami yang dilakukan atas inisiatif para istri dengan mendapatkan persetujuan  suami. Poligami ulama Madura dipengaruhi oleh faktor kebutuhan seksual dan otoritas ulama Madura, serta budaya hidup masyarakat Madura yang taat beragama dan cenderung berlebihan dalam mengkultus ulamanya.